A fast parallel decoding algorithm for general one-point AG codes with a systolic array architecture - Kurihara, M.; Sakata, S. (Proceedings 1995 IEEE International Symposium on Information Theory, 1995)
We propose a fast parallel decoding algorithm for general one-point algebraic geometric (1-pt AG) codes with a systolic array architecture (SAA). This algorithm is able to correct up to half the Feng-Rao (see IEEE Trans. IT, vo1.39, no.1, p.37-45, 1993) bound and the time complexity is O(n) by using a series of O(n) processors where n is the code length and each processor is composed of /spl tau/ cells for the smallest non-zero and non-gap value /spl tau/.